Model Pengelolaan Ilngkungan Hidup Berwawasan Gender untuk mendukung Pembangunan Berkelanjutan - Astuti, Ismi Dwi; Utami, Trisni; Sudarwanto, Sentot (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2009)
This research underline the strategies to manage the environment based on gender equity perspective and is qualitative in nature. Data were gathered by interviews and focused group discussions. This research produces a model of environmental management based on gender equity perspectives, called GEBEM (Gender Equity Based Environmental Management). It is intended specifically to be a strategic guidance for managing the environment of the Laweyan area by enhancing equal opportunities for both men and women to participate in and control the environmental management of the area.